Inovasi Pembelajaran Anak Usia Dini dalam Era Digital - Agus Niada Lawolo (JURNAL TALITAKUM: JURNAL PENDIDIKAN KRISTEN ANAK USIA DINI, 2025)
The development of digital technology has brought significant changes to education, including early childhood education (ECE). Today’s generation of children grows up surrounded by rapid technological advances, requiring learning processes to adapt through relevant and engaging innovations. This article aims to describe various forms of early childhood learning innovations in the digital era, their benefits for children’s development, as well as the challenges and strategies for their implementation. This study employs a descriptive qualitative approach using library research based on national and international literature. The findings show that innovations such as interactive learning media, digital storytelling, blended learning, and Augmented Reality (AR) and Virtual Reality (VR) technologies are effective in enhancing children’s motivation, creativity, and digital literacy. However, implementation still faces challenges such as low digital literacy among teachers and parents, unequal access to technology, and the risk of gadget addiction. Therefore, training, guidance, and the application of digital balance principles are needed to ensure that learning innovations are implemented effectively while remaining grounded in children’s character and spiritual values.